PERTIMBANGAN HAKIM PENGADILAN AGAMA DALAM PERKARA PUTUSAN DISPENSASI KAWIN PERSPEKTIF PERUNDANG-UNDANGAN DAN FILSAFAT HUKUM ISLAM Kajian Putusan Nomor 0026/Pdt.P/2019/PA.Mt - Iwannudin Iwannudin (JAS : Jurnal Ahwal Syakhshiyyah, 2021)
The study aims to determine the judges basis consideration at the Religious Court of Metro City Lampung in the Case of Marriage Dispensation Decision in the perspective of Indonesian and Islamic Law Philosophy as a relief from obligations and prohibitions for men and women who have not met the age requirements for marriage. Men reach the 19 years and women 16 years which are allowed to marry under Law No.1 of 1974 concerning Marriage. What then happened was a renewal in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974. Marriage is only permitted if the man and woman have reached the age of 19 years. While in Islam the purpose of these rules is found in the Maqashid Syari'ah theory that the purpose of the formation of laws is for the benefit of mankind. The panel of judges is guided by Law No.1 of 1974 on Marriage and Compilation of Islamic Law. The Panel of Judges did not pay attention to the values stated in Law No.4 of 1979 concerning Child Welfare, TAP. No. XVII/MPR/1998. on Human Rights, Law no. 39 of 1999 concerning Human Rights, Law No.23 of 2002 concerning Child Protection.